New records of mealybug species in Iran with discussions on morphological variations (Hemiptera, Coccoidea: Pseudococcidae) - Moghaddam, Masumeh (Entomologica Fennica, 2015)
The mealybug Vryburgia succulentarum Williams is recorded for the first time from the Palaearctic area (in a greenhouse). In addition, four other species, Artemisia bispinus (Borchsenius), Coccura circumscripta (Kiritchenko), Mirococcus inermis (Hall) and Phenacoccus daganiae (Bodenheimer) are recorded for the first time from Iran. Artemisia bispinus, C. circumscripta and P. daganiae have been reported only from the Palaearctic Region. The third-instar female of M. inermis is described based on specimens collected in Iran. Some characters of A. bispinus, C. circumscripta and M. inermis differ from those in the specimens found elsewhere and are discussed. Illustrations, localities and host plants of the above species are provided.